Development of a Hybrid Bioethanol–Seawater Electrolyte from Oil Palm Empty Fruit Bunch Waste for Sustainable Bio-Battery Applications - Dwi Syafitri; Muhammad Yerizam; Rusdianasari (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
The increasing demand for renewable energy necessitates innovative solutions utilizing abundant agricultural waste. This study investigates the development of a novel hybrid liquid electrolyte that combines crude bioethanol derived from oil palm empty fruit bunches (OPEFB) with natural seawater for sustainable bio-battery systems. The main novelty lies in leveraging the synergistic effect between the stable, polar organic medium of OPEFB bioethanol and the high conductivity of seawater (49.87 mS/cm), thereby eliminating reliance on synthetic chemicals. The OPEFB underwent delignification (6% NaOH) and hydrolysis prior to fermentation. Gas Chromatography-Mass Spectrometry (GC-MS) confirmed the successful bioconversion into crude bioethanol (39.84% relative peak area). Electrochemical evaluations using a Zn/Cu electrode configuration revealed that the delignification-based solution at an optimal 70:30 (bioethanol-to-seawater) mixture ratio generated a maximum power output of 0.84 mW. Significantly, this research provides a dual-solution approach: valorizing massive lignocellulosic waste while advancing eco-friendly energy storage. Practically, the formulated hybrid bio-battery is highly viable for ultra-low-power applications, demonstrably capable of continuously powering small Light Emitting Diodes (LEDs) for up to 24 hours and mini DC fans for 9 hours. Contribution to Sustainable Development Goals (SDGs):SDG 7: Affordable and Clean EnergySDG 9: Industry, Innovation, and InfrastructureSDG 12: Sustainable consumption and productionSDG 13: Climate Action